GENETIC DIVERSITY AND ASSOCIATION ANALYSIS OF SALT TOLERANCE IN ASIATIC COTTON (GOSSYPIUM ARBOREUM) WITH MOLECULAR MARKERS - Tussipkan, D.; Pan , Zh.; Gong, W.; Dai, P.; Manabayeva, Sh.; Du , X. (Eurasian Journal of Applied Biotechnology, 2024)
Gossypium arboreum possesses favorable characteristics that are valuable for developing superior cotton cultivars. This study was carried out to analyze genetic diversity and identify marker-trait association analysis related to salt tolerance using SSR markers for 215 accessions of G. arboreum. The salt tolerance-related traits like germination rate, fresh weight, stem length, water content, chlorophyll content, electric conductivity, and MDA of the accessions were identified using 150 mM salt for 7 days of seedling growth. According to the comprehensive index of salt tolerance, 215 accessions were categorized mainly into four groups. Twenty four accessions were classified as highly tolerant to salt treatment (>2.5). The natural population was classified into 3 main groups by phylogenetic analysis. The classifications of phylogenetic analysis were largely congruent with the breeding history and ecological region. Twenty-two strong marker-trait associations were obtained with strict significant P value i.e. P< 0.01 and four makers including NAU1023, NAU1099, JESPR222, and NAU2783 were significantly related to salt tolerance. The marker NAU2783 was highest associated (P= 1.98E-12) with relative electric conductivity, and with the highest phenotype variation of 20.87%. Some markers are significantly associated with more than two traits. MUSS020 was significantly (P<0.01) associated with relative fresh weight, and relative MDA, NAU1375 was associated with relative fresh weight and relative stem length, while NAU3468 was significantly associated with relative fresh weight, relative germination rate, and relative water content. The strong marker-trait association results might provide insights for marker-assistant selecting salt-tolerant varieties and will be useful for future cotton breeding programs.